2012
DOI: 10.1111/j.1464-5491.2011.03385.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatic injury following treatment of a long‐acting insulin analogue overdose necessitating urgent insulin depot excision

Abstract: This report highlights the risk of acute hepatic injury during the treatment of insulin overdose and the importance of careful glucose supplementation. It also demonstrates how earlier excision of an insulin depot could potentially prevent this problem and hasten recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Another reported treatment involves excision of the insulin depot from the subcutaneous tissue if a large area of fluctuance is apparent (3,4). Hemodialysis is also known to remove insulin from the blood and theoretically could be used if fluid overload is a concern, but it has not yet been used in cases of insulin overdose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another reported treatment involves excision of the insulin depot from the subcutaneous tissue if a large area of fluctuance is apparent (3,4). Hemodialysis is also known to remove insulin from the blood and theoretically could be used if fluid overload is a concern, but it has not yet been used in cases of insulin overdose.…”
Section: Discussionmentioning
confidence: 99%
“…Massive amounts of dextrose-containing fluids are given intravenously which can cause fluid overload and lead to pulmonary edema. It has also been reported that massive glucose supplementation may lead to acute liver injury (1,3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Other strategies suggested for managing prolonged hypoglycaemia following insulin overdose include surgical excision of the depot site, the use of glucocorticoids to induce insulin resistance and the use of glucagon to alleviate the need for glucose loading. 2,4 The obvious dearth of reported literature and limited knowledge in this area can lead to unnecessary investigations, anxiety for the patient and also prolonged hospital length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…While the management of hypoglycaemia takes a priority to prevent neurological injury, other complications such as hypokalaemia, hypomagnesaemia, pulmonary oedema and hepatic dysfunction also need to be monitored carefully. 3,4 Glargine is a long acting peakless basal insulin which is deposited in the subcutaneous tissue in a polymeric form with gradual release for prolonged action. 5 The pharmacokinetic profile of glargine can be predicted for physiologic doses, but it becomes difficult to identify the pattern and duration of release of this long acting insulin following a massive overdose.…”
Section: Discussionmentioning
confidence: 99%